Semi-analytic modeling and experimental verification of arbitrary aero-engine complex spatial pipeline - Chen, Weijiao; Guo, Ziwei; Chen, Shuo; Cao, Yiming; Guo, Xumin; Ma, Hui; Wen, Bangchun (Applied mathematical modelling, 2024)
•A semi-analytical method is adopted for arbitrary fluid-conveying spatial pipeline.•The actual flexible-bracket clamp stiffness is considered.•Virtual springs are used for the straight-curved connection. In-depth research is imperative for complex spatial pipelines with fluid-structure interaction. A comprehensive and universal three-dimensional semi-analytical modeling method is first established for complex fluid-conveying spatial pipelines under the base excitation with arbitrary connections and configurations under different boundary conditions. The virtual spring technology is used to connect the straight and curved pipeline segments with spatial angles and simulate boundary conditions. For a thorough analysis, the actual stiffness of the bracket-clamp system is experimentally measured for the first time. The multi-level coupling dynamic model of part, component, and system levels under actual boundary conditions is established. An efficient method for solving the fluid-structure coupling pipeline system dynamics considering the base excitation is proposed based on energy method. The mid-plane displacement function of the Fourier series is introduced and solved using the principle of modal superposition. Hammer impact modal experiments, ANSYS software and vibration response experiments are performed on spatial pipelines supported by flexible bracket-clamps; the numerical and experimental results support the semi-analytical results. The degenerate model is verified with the simple plane pipelines in other references, and the errors are less than 5 %. The proposed method exhibits broad applicability and generalizability, making it suitable for various configurations and boundary conditions.